Photo showing the replacement of the stockade at Bethabara, 1964. - (:unkn) unknown (Forsyth County Public Library)
WSJ 12-14-64 p.1.
Photo showing the replacement of the stockade at Bethabara, 1964.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth